Application of open-path Fourier transform infrared spectroscopy (OP-FTIR) to measure greenhouse gas concentrations from agricultural fields - C.-H. Lin; R. H. Grant; A. J. Heber; C. T. Johnston; C. T. Johnston (Atmospheric Measurement Techniques, 2019)
Open-path Fourier transform infrared spectroscopy (OP-FTIR) has often been used to measure hazardous or trace gases from hot point sources (e.g. volcano, industrial, or agricultural facilities) but seldom used to measure greenhouse gases (GHGs) from field-scale sources (e.g. agricultural soils). Closed-path mid-IR laser-based N2O, nondispersive-IR CO2 analysers, and OP-FTIR were used to measure concentrations of N2O and CO2 at a maize cropping system during 9–19 June 2014. To measure N2O and CO2 concentrations accurately, we developed a quantitative method of N2O∕CO2 analysis that minimized interferences from diurnal changes of humidity and temperature. Two chemometric multivariate models, classical least squares (CLS) and partial least squares (PLS), were developed. This study evaluated various methods to generate the single-beam background spectra and different spectral regions for determining N2O and CO2 concentrations from OP-FTIR spectra. A standard extractive method was used to measure the actual path-averaged concentrations along an OP-FTIR optical path in situ, as a benchmark to assess the feasibilities of these quantitative methods. Within an absolute humidity range of 5000–20 000 ppmv and a temperature range of 10–35 ∘C, we found that the CLS model underestimated N2O concentrations (bias =-4.9±3.1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="62pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="1199c60d5da8ecf5da7795e506317b9d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-12-3403-2019-ie00001.svg" width="62pt" height="10pt" src="amt-12-3403-2019-ie00001.png"/></svg:svg> %) calculated from OP-FTIR spectra, and the PLS model improved the accuracy of calculated N2O concentrations (bias =1.4±2.3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="4cf55b45aaf6347f81021eebb53ce659"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-12-3403-2019-ie00002.svg" width="54pt" height="10pt" src="amt-12-3403-2019-ie00002.png"/></svg:svg> %). The bias of calculated CO2 concentrations was -1.0±2.8<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="52pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="80143b66c290d40986e3425df7c2a702"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-12-3403-2019-ie00003.svg" width="52pt" height="10pt" src="amt-12-3403-2019-ie00003.png"/></svg:svg> % using the CLS model. These methods suggested that environmental variables potentially lead to biases in N2O and CO2 estimations from OP-FTIR spectra and may help OP-FTIR users avoid dependency on extractive methods of calibrations.